Could CD8/38 predict virological response to antiretroviral therapy (ART) in human immunodeficiency virus (HIV) infected patients? - Umi S. Intansari; Yanri W Subronto; Yunika Puspa Dewi; Adika Zhulhi Arjana; Mohammad Juffrie; Marsetyawan HNE Soesatyo; Budi Mulyono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
ABSTRACT The success rate of antiretroviral therapy (ART) depends on the efficacy of the drug and the immune system’s ability to control virus replication. Viral load (VL) examination is a standard test for ART monitoring. Unfortunately, this test is still very limited, especially in Indonesia. CD38 expression has been studied as a predictor for disease progression and decreases once ART is initiated. The aim of this study was to evaluate the possible usage of declining CD8/38 T-cell percentages in predicting the VL. Forty-five subjects naïve to ART were evaluated in this observational analytic study with a prospective design. Data collected included the medical history, physical examination, WHO clinical staging, complete blood counts, CD4 cell count, and plasma VL. These data then reevaluated six months after ART initiation. A paired t-test, and correlation test were used to analyze the data. Significant differences were found in all of the laboratory parameters between pre and post ART. There was a weak significant positive correlation between declining CD8/38 T-cell percentages and declining VL after 6 months of ART (r=0.33; p=0.026), with r2 = 0.11. Therefore despite the linear relationship, CD38 has limited value for prediction of VL.